Prospects of sea buckthorn (Hippophae rhamnoides L.) polysaccharides: preparation, structural characterization, and bioactivities diversity - Shuyuan Shi; Ruiyun Wu; Zixin Han; Yu Sun; Pinglan Li; Fazheng Ren; Nan Shang (Food Science and Human Wellness)
Sea buckthorn (Hippophae rhamnoides L.) is a natural homologous substance of medicine and food. Polysaccharide, as one of its primary active components, has very superior biological activity and can be used as a dietary supplement for functional foods, with good commercial prospects. Although initial progress has been made in the study of sea buckthorn polysaccharides, related studies have been fragmented and lacked systematic and generalization. This manuscript presents a critical analysis and systematic summary of the extraction and purification methods, structural characterization and physicochemical properties, biological activity and potential mechanisms, and structure-activity relationships of sea buckthorn polysaccharides. Accumulating evidence has indicated that sea buckthorn polysaccharides, which were widely prepared by water extraction and column chromatography purifications, exhibited exhibit superior biological activities in vitro and in vivo, including antioxidant, immunomodulatory, anti-inflammatory, hepatorenal protective, antibacterial, antiviral, and prebiotic activities. After analysis, it was concluded that there is a correlation between the relevant activities of sea buckthorn polysaccharides and that the structure of sea buckthorn polysaccharides has a great influence on their biological activity. We reviewed the challenges and limitations of sea buckthorn polysaccharides, summarized the critical aspects, and provided suggestions for potential breakthroughs in the research and application of sea buckthorn polysaccharide.